STUDIES OF THE TYPES OF VARIOUS NAMES IN THE GENUS NOTHOPEGIA BLUME (ANACARDIACEAE) - Deepu, S.; Geethakumary, M. P.; Pandurangan, A. G. (Phytotaxa, 2018)
The typification of six names in Nothopegia (Anacardiaceae) viz. N. aureo-fulva, N. beddomei, N. racemosa, N. racemosa var. angustifolia, N. heyneana and N. travancorica, is discussed and lectotypes designated.